Ethical Decision-Making and Artificial Intelligence in Nursing Education: An Integrative Review - Şengül, Tuba; Sarıköse, Seda; GÜL, ASİYE (Sage Publishing, 2025)
The integration of artificial intelligence technologies is transforming healthcare and nursing education, offering significant benefits for patient care and professional development. However, as their use grows, it is crucial to address the ethical implications to ensure that fundamental principles like justice and integrity are maintained in both clinical and educational settings. The aim of this integrative review is to explore the ethical challenges, risks, and future perspectives of integrating artificial intelligence into nursing education. It examines how these tools influence ethical decision-making processes, identifies critical barriers, and proposes strategies for ethical implementation. Following an integrative review methodology, 184 articles were identified, with 124 remaining after duplicate removal. Fifteen peer-reviewed studies analyzed. The methodological quality of the included studies was assessed using appropriate Joanna Briggs Institute Critical Appraisal Checklists based on study design. Searches were conducted in the PubMed, Cochrane Library, MEDLINE (Ovid), Scopus, Web of Science, CINAHL, and ScienceDirect databases from 2014 to September 2024. Data was analysed using constant comparative analysis. The review is registered in the PROSPERO database (CRD42024609440). Guided by Rest's Four-Component Model of Moral Behavior, the synthesis was organized under four components. Moral Sensitivity included themes such as ethical and psychosocial effects, data privacy, equity in access, and cultural sensitivity. Moral Judgment covered ethical reasoning skills, AI accuracy, bias, and academic integrity. Moral Motivation addressed over-reliance on AI and the need for ethical frameworks. Moral Character highlighted educator roles and research priorities for ethical AI use. Artificial intelligence offers transformative opportunities for nursing education, but also presents significant ethical challenges. To ensure its responsible integration, nursing curricula must adopt clear ethical frameworks, equip educators with the skills to guide students and address disparities in access.
Keywords: Artificial Intelligence; ChatGPT; Ethical Decision-making; Integrative Review; Nursing Education